2020
DOI: 10.1200/jco.2020.38.4_suppl.281
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled phase III multicenter study on dose escalation in definitive chemoradiation for patients with locally advanced esophageal cancer: ARTDECO study.

Abstract: 281 Background: To analyze the effect of radiation dose escalation to the primary tumor on local control, locoregional control, survival and toxicity in definitive chemoradiation for esophageal cancer. Methods: Patients with clinical stage T2-4, N0-3, M0 carcinoma of the esophagus were randomized between a standard dose of 50.4 Gy/1.8 Gy/5,5 weeks to the tumor and regional lymph nodes (SD) versus the same dose combined with an integrated boost of 0,4 Gy per fraction (total 61,6 Gy) to the primary tumor (HD). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
38
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 0 publications
5
38
0
1
Order By: Relevance
“…However, escalated radiation dose resulted in numerical increase in toxicity but did not improve the overall survival. [ 16 ] In line with the ARTDECO trial, the present study did not observe the benefit in local disease control or survival from increasing radiation dose in our whole cohort. Interestingly, we found that increasing radiation dose to more than 60 gray in patients with large primary tumor volume (≥ 55.3 cm 3 ) can improve local disease control and overall survival ( Fig 4 ).…”
Section: Discussionsupporting
confidence: 87%
“…However, escalated radiation dose resulted in numerical increase in toxicity but did not improve the overall survival. [ 16 ] In line with the ARTDECO trial, the present study did not observe the benefit in local disease control or survival from increasing radiation dose in our whole cohort. Interestingly, we found that increasing radiation dose to more than 60 gray in patients with large primary tumor volume (≥ 55.3 cm 3 ) can improve local disease control and overall survival ( Fig 4 ).…”
Section: Discussionsupporting
confidence: 87%
“…Our meta-analysis showed that although esophagus-related toxicity and pulmonary injury were the main severe late toxicities, high radiation dose did not increase the toxicities, which finally convert to the survival benefit. Two nearly closed RCTs reported the initial results by conference abstracts, which could not be included in this study (37,38). Xu et al (37) showed no difference toward 1 and 2 y-OS or treatment toxicity between the HD-RT (60 Gy) and LD-RT (50 Gy) groups.…”
Section: Discussionmentioning
confidence: 97%
“…Two nearly closed RCTs reported the initial results by conference abstracts, which could not be included in this study ( 37 , 38 ). Xu et al ( 37 ) showed no difference toward 1 and 2 y-OS or treatment toxicity between the HD-RT (60 Gy) and LD-RT (50 Gy) groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the era of modern RT techniques, dose escalation in CRT for EC has been investigated in 260 patients with EC by the randomized ARTDECO study, including 72 patients (28%) with proximal EC. Radiation dose escalation up to 61.6 Gy versus 50.4 Gy to the primary tumor in CP-based CRT did not improve local control and OS [32].…”
Section: Discussionmentioning
confidence: 80%